Management of Fever in Postpneumococcal Vaccine Era: Comparison of Management Practices by Pediatric Emergency Medicine and General Emergency Medicine Physicians - Khine, Hnin; Goldman, David L.; Avner, Jeffrey R. (Emergency Medicine International, 2014)
Background. The primary objective of this study was to compare management practices of general emergency physicians (GEMPs) and pediatric emergency medicine physicians (PEMPs) for well-appearing young febrile children. Methods. We retrospectively reviewed the charts of well-appearing febrile children aged 3–36 months who presented to a large urban children’s hospital (PED), staffed by PEMPs, or a large urban general emergency department (GED), staffed by GEMPs. Demographics, immunization status, laboratory tests ordered, antibiotic usage, and final diagnoses were collected. Results. 224 cases from the PED and 237 cases from the GED were reviewed. Children seen by PEMPs had significantly less CXRs (23 (10.3%) versus 51 (21.5%), P=0.001) and more rapid viral testing done (102 (45%) versus 40 (17%), P<0.0001). A diagnosis of a viral infection was more common in the PED, while a diagnosis of bacterial infection (including otitis media) was more common in the GED. More GED patients were prescribed antibiotics (41% versus 27%, P=0.002), while more PED patients were treated with oseltamivir (6.7% versus 0.4%, P< 0.001). Conclusions. Our findings identify important differences in the care of the young, well-appearing febrile child by PEMPs and GEMPs and highlight the need for standardization of care.